2005
DOI: 10.2174/138945005774574425
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in PACU: The Role of Propofol

Abstract: In critically ill patients, adequate sedation increases comfort, minimizes stress response and facilitates diagnostic and therapeutic procedures. Propofol (2-, 6-diisopropylphenol) is an intravenous sedative-hypnotic agent popular for sedation in the Intensive Care Unit. The favorable propofol pharmacokinetic, characterized by a three compartment linear model, allows rapid onset and short duration of action. The emergence time from sedation with propofol varies with the depth and the duration of sedation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…This finding disagrees with that of Egwu et al, [15], who reported a decrease in respiratory rate after AA administration in rabbits. The result of the present study showed that propofol when administered alone decreased the respiratory rate only after induction, which agreed with the result obtained by De Cosmo et al, [31] that propofol possesses profound respiratory depressant properties in humans. Goats administered with 300 mg/kg AA before propofol induction showed a decrease in respiratory rate during induction.…”
Section: Discussionsupporting
confidence: 94%
“…This finding disagrees with that of Egwu et al, [15], who reported a decrease in respiratory rate after AA administration in rabbits. The result of the present study showed that propofol when administered alone decreased the respiratory rate only after induction, which agreed with the result obtained by De Cosmo et al, [31] that propofol possesses profound respiratory depressant properties in humans. Goats administered with 300 mg/kg AA before propofol induction showed a decrease in respiratory rate during induction.…”
Section: Discussionsupporting
confidence: 94%
“…[1][2][3] Since these patients may already be immunosuppressed by preexisting diseases, surgical trauma, and/or overwhelming infection, 4,5 even small adverse effects on immunity, due to the sedative, could be devastating for such patients.…”
Section: Résumémentioning
confidence: 99%
“…Propofol gains it's popularity because it has a rapid onset and offset compared with other commonly used ICU sedatives. (9) Besides the relation to stress response, the ICU stay may lead to psychological problems as well. Many patients developing post-traumatic stress syndromes have reported memories of vivid nightmares, hallucinations and altered sense of reality after their discharge from the ICU.…”
Section: Effect To Respiratory Systemmentioning
confidence: 99%